Validation of a prognostic score for hidden cancer in unprovoked venous thromboembolism - Jara-Palomares, Luis; Otero, Remedios; Jimenez, David; Praena-Fernandez, Juan Manuel; Font, Carme; Falga, Conxita; Soler, Silvia; Riesco, David; Verhamme, Peter; Monreal, Manuel; on behalf of RIETE Registry (PLOS ONE, 2018)
The usefulness of a diagnostic workup for occult cancer in patients with venous thromboembolism (VTE) is controversial. We used the RIETE (Registro Informatizado Enfermedad Trombo Embólica) database to perform a nested case-control study to validate a prognostic score that identifies patients with unprovoked VTE at increased risk for cancer. We dichotomized patients as having low- (≤2 points) or high (≥3 points) risk for cancer, and tried to validate the score at 12 and 24 months. From January 2014 to October 2016, 11,695 VTE patients were recruited. Of these, 1,360 with unprovoked VTE (11.6%) were eligible for the study. At 12 months, 52 patients (3.8%; 95%CI: 2.9–5%) were diagnosed with cancer. Among 905 patients (67%) scoring ≤2 points, 22 (2.4%) had cancer. Among 455 scoring ≥3 points, 30 (6.6%) had cancer (hazard ratio 2.8; 95%CI 1.6–5; p<0.01). C-statistic was 0.63 (95%CI 0.55–0.71). At 24 months, 58 patients (4.3%; 95%CI: 3.3–5.5%) were diagnosed with cancer. Among 905 patients scoring ≤2 points, 26 (2.9%) had cancer. Among 455 patients scoring ≥3 points, 32 (7%) had cancer (hazard ratio 2.6; 95%CI 1.5–4.3; p<0.01). C-statistic was 0.61 (95%CI, 0.54–0.69). We validated our prognostic score at 12 and 24 months, although prospective cohort validation is needed. This may help to identify patients for whom more extensive screening workup may be required.